2003
DOI: 10.1152/jn.00397.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential and History-Dependent Modulation of a Stretch Receptor in the Stomatogastric System of the Crab,Cancer borealis

Abstract: Neuromodulators can modify the magnitude and kinetics of the response of a sensory neuron to a stimulus. Six neuroactive substances modified the activity of the gastropyloric receptor 2 (GPR2) neuron of the stomatogastric nervous system (STNS) of the crab Cancer borealis during muscle stretch. Stretches were applied to the gastric mill 9 (gm9) and the cardio-pyloric valve 3a (cpv3a) muscles. SDRNFLRFamide and dopamine had excitatory effects on GPR2. Serotonin, GABA, and the peptide allatostatin-3 (AST) decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…Responses of individual neurons, synapses, and circuits to neuromodulation are often quite variable (50,51). In some instances, it is clear that the effect of the modulator depends on some obvious feature of the state of the preparation (52)(53)(54)(55)(56). In some instances, this variability arises from unknown sources and is likely a consequence of differing underlying cell or circuit parameters.…”
Section: Parameter Compensation and Correlationsmentioning
confidence: 99%
“…Responses of individual neurons, synapses, and circuits to neuromodulation are often quite variable (50,51). In some instances, it is clear that the effect of the modulator depends on some obvious feature of the state of the preparation (52)(53)(54)(55)(56). In some instances, this variability arises from unknown sources and is likely a consequence of differing underlying cell or circuit parameters.…”
Section: Parameter Compensation and Correlationsmentioning
confidence: 99%
“…Another level of control in this system is suggested by the fact that the sensitivity of GPR to muscle stretch is itself modulated (Birmingham, 2001;Birmingham et al, 2003). We therefore anticipate that our appreciation for how sensory signals regulate neural circuit activity will be extended further as we assess the consequences resulting from modulation of GPR sensitivity for its influence on the gastric mill motor circuit.…”
Section: Presynaptic Inhibition Enables Sensory Signals To Dynamicallmentioning
confidence: 99%
“…cockroaches, crickets and termites (Stay and Tobe, 2007). A-type peptides have also been found in a number of crustaceans (Duve et al, 1997;Dircksen et al, 1999;Duve et al, 2002;Huybrechts et al, 2003;Fu et al, 2005;Yasuda-Kamatani and Yasuda, 2006;Yin et al, 2006;Christie et al, 2008a;Ma et al, 2008;Gard et al, 2009;Ma et al, 2009), where they have been shown to function as locally released and/or hormonally delivered neuro/myomodulators (Skiebe and Schneider, 1994;Jorge-Rivera and Marder, 1997;Jorge-Rivera et al, 1998;Dircksen et al, 1999;Kreissl et al, 1999;Birmingham et al, 2003;Billimoria et al, 2006;Cruz-BermĂșdez and Marder, 2007). Molecular, biochemical and mass spectral analyses have shown that multiple isoforms of A-type peptides are common in both insect and crustacean species, with multiple peptides encoded by the known arthropod A-AST prepro-hormones (e.g.…”
Section: Introductionmentioning
confidence: 99%